Does 11.5 mm guided single port surgery has clinical advantage than multi-port thoracoscopic surgery in spontaneous pneumothorax? - Jeon, Hyun Woo; Kim, Young-Du (Journal of Thoracic Disease, 2016)
Background: Video-assisted thoracoscopic surgery (VATS) has been widely used for spontaneous pneumothorax (SP). In recent years, thoracic surgeons have attempted single incision or single port surgery with the development of surgical technology and skills. Theoretically, single port surgery is expected to provide benefits such as less pain and early recovery. The purpose of this study was to determine the benefits of single port surgery in SP. Methods: The 107 patients with SP who underwent surgery, between July 2013 and May 2015, were reviewed retrospectively. The patients with secondary pneumothorax, who underwent open procedures and lacking of medical records were vexcluded. Visual analog scale (VAS), paresthesia and clinical outcomes were reviewed in 86 patients (46 patients: three-port, 40 patients: 11.5 mm guided single-port). Results: The mean age was 23.4 years in three-port and 22.4 in single-port (P=0.247). The height and body weight were not significantly difference between two groups. The mean operation time was 39 minutes (mins) in the three-port and 37.3 mins in the single port without statistical difference (P=0.204). The pain score in the single port surgery was significantly lower after postoperative day (POD) 1 (P=0.028). However chest tube duration time was significantly shorter in the single port group (P